2021
DOI: 10.1177/1097184x211023545
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Manhood: Race, Class, and Masculinity in Men’s Attraction to Guns and Aggression

Abstract: Using an original self-report survey of 18- to 30-year-old men, this study aims to understand gendered processes underlying men’s attitudes toward guns and aggressive behavior through two types of threats. We find that acceptance threat, a threat to an individual man’s sense of masculinity, and status threat, the belief that societal changes disadvantage men as a group, are positively associated with both men’s attraction to guns and their aggressive reactions to perceived disrespect. The effect of acceptance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…For example, Stange and Oyster (2000) argued that firearms are a symbol for men's "power, force, aggressiveness, decisiveness, deadly accuracy, [and] cold rationality" (p. 22). Similar arguments have been made connecting firearms as symbols of masculine aggression, self-reliance, and domination (Melzer, 2009;O'Neill, 2007;Scaptura & Boyle, 2021;Stroud, 2012), themes conceptually similar to those commonly understood to comprise traditional masculine ideology (Levant et al, 2013;Levant & Richmond, 2016).…”
Section: Firearms and Masculinitymentioning
confidence: 66%
See 3 more Smart Citations
“…For example, Stange and Oyster (2000) argued that firearms are a symbol for men's "power, force, aggressiveness, decisiveness, deadly accuracy, [and] cold rationality" (p. 22). Similar arguments have been made connecting firearms as symbols of masculine aggression, self-reliance, and domination (Melzer, 2009;O'Neill, 2007;Scaptura & Boyle, 2021;Stroud, 2012), themes conceptually similar to those commonly understood to comprise traditional masculine ideology (Levant et al, 2013;Levant & Richmond, 2016).…”
Section: Firearms and Masculinitymentioning
confidence: 66%
“…Mencken & Froese, 2019) is positively associated with masculine role attitudes. Similarly, Scaptura and Boyle (2021) findings suggest the connection between masculinity and firearms to be fear based (e.g., men's loss of traditional privilege). Moreover, research from masculine contingency has shown that masculine threats compared to masculine boosts are more strongly related to dysfunctionality such as gender role conflict, hostile sexism, homophobia, while also being significantly inversely related to self-esteem (Burkley et al, 2016).…”
Section: Masculinity Boostmentioning
confidence: 93%
See 2 more Smart Citations
“…Continuing to draw from feminist traditions, we recognize this conversation is inherently political (Hanisch, 1970), and that restructuring society requires not only individually redefining masculinity, but a reorientation of mainstream political values. For example, we can apply our framework to better understand the “politics of domination” (hooks, 1994, p. 289) where hegemonic, White masculinity holds sway in the U.S. political arena (DiMuccio & Knowles, 2020), and is framed as a threatened status which must then be reasserted violently (Harrison & Michelson, 2019; Helms, 2016; Scaptura & Boyle, 2021), as compared to a politics of care and connection that uses power to protect the vulnerable and change unjust systems.…”
Section: Need For Systemic Changementioning
confidence: 99%